Effects of Water Exercise Training on Motor Symptoms and Physical Pains of Postmenopausal Women with Knee Osteoarthritis: A Randomized Clinical Trial - Mohammad Reza Moharrami; Abbasali Dorosti; Behrouz Nazari (Mashhad University of Medical Sciences, 2021)
Introduction: Menopause is one of the risk factors for knee osteoarthritis which causes complications such as pain and movement restriction. Involving people in treatment programs such as self-care interventions has been associated with beneficial results. This study was performed with aim to evaluate the effects of water exercise training on motor symptoms and physical pains in postmenopausal women with knee osteoarthritis. Methods: This randomized clinical trial study was performed with participation of 42 women in Tabriz University of Medical Sciences in 2019. After random assignment of the subjects to the intervention and control groups, the intervention group performed simple water exercises for 12 sessions (50 minutes each session). Data were collected using Knee injury and osteoarthritis outcome score questionnaire. Data were analyzed by SPSS software (version 20) and Kolmogorov-Smirnov, Fisher exact, Chi-square and independent t-test. P<0.05 was considered statistically significant. Results: The mean total score of osteoarthritis in the intervention group before the intervention was 121.15 ± 12.90 and in the control group was 129.19 ±11.49, which was not significantly different (p= 0.209), but after receiving the intervention, statistically significant difference was observed between the intervention group (74.81 ± 5.55) and the control group (127.12 ± 11.89) (p= 0.0001). Conclusion: Simple water exercises improve physical pain and osteoarthritis symptoms in postmenopausal women.